PELATIHAN PERANGKAT PEMBELAJARAN BERBASIS ONLINE BAGI GURU RA-ISLAM NUR KOTA MEDAN - Simamora, Minta Ito; Simamora, Yumira; Syarah, Fatmah; Yusnika, Yusnika (JALIYE: Jurnal Abdimas, Loyalitas, dan Edukasi, 2024)
Most RA teachers still face challenges in developing online learning tools that suit children's needs. Technological skills and appropriate pedagogical approaches are determining factors for the success of online teaching at the RA level. The aim is to increase teacher competency, increase student involvement and change learning approaches. The methods that will be used are Initial Information Collection, Training Design, Training Implementation, Learning Tool Development, and Learning Tool Testing. an overview of the results that have been achieved as well as a discussion regarding the impacts and changes that occurred after attending the training. Community service in the form of online learning tool development training for RA teachers has had a significant impact in improving competence and skills in online learning. concluded that this training had a positive impact on the student learning experience, encouraging more active and interactive involvement. The results of the implementation are, More than 90% of RA teachers actively participate in all training sessions. The training modules are designed to provide an in-depth understanding of the basic concepts of developing online learning tools. RA teachers have developed online learning tools based on the modules provided. have been studied, the learning tools developed are tested with students. The results of the trials are used to make improvements and adjustments, producing devices that are more effective and suit the characteristics of young children.